Arabic Teachers: Professional Competence and Reflective Teaching - Ilmiani, Aulia Mustika; Marsiah, Marsiah; Nuryaman, Adelina Dewi; Salim, Oemar (Jurnal Al-Maqoyis, 2023)
This article discusses the professional competence of Arabic language teachers in several schools in the Central Kalimantan region which have not been met according to the standards set by the Regulation of the Minister of National Education of the Republic of Indonesia Number 16 of 2007 concerning Academic Qualification Standards and Teacher Competency. Research using qualitative method. Through the results of the research, three Arabic teachers were found with inappropriate educational backgrounds. However, in the learning reflection process, the three Arabic teachers carried out various reflection activities, such as learning evaluation, classroom action research, self-study, self-observation, and student responses, attending training, implementing innovations, recording the learning process, analyzing needs. students, and address the needs of students by needs analysis. From the results of this study, the researcher recommends that Arabic teachers reflect regularly to improve the quality of learning and meet established professional competency standards.